2007
DOI: 10.1002/ejoc.200600794
|View full text |Cite
|
Sign up to set email alerts
|

A New Biomimetic‐Like Aromatization of the Cyclic End Groups of Terpenoids with Stereospecific Migration of One of the Methyl Groups: A Convenient Route to Isorenieratene (ϕ,ϕ‐Carotene)

Abstract: The synthesis of isorenieratene, a natural carotenoid isolated from the marine sponge Reniera japonica and from some anoxygenic phototrophic bacteria or nonphotosynthetic actinomycetes, was performed from α‐, β‐ and retro‐ionones. In this series of cyclohexenes, this synthesis is the first to include a one‐pot aromatization of the cyclic end group with concomitant regioselective migration of one methyl group from the gem dimethyl functionality. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Ketone 4 , which is a natural product with a pleasant floral scent, was previously synthesized by the palladium‐catalyzed arylation of 2,3,6‐trimethylbromobenzene with 3‐butene‐2‐one . A few examples in the literature have shown that ketone 4 can also be formed directly from ionones . The microbial oxidation of β‐ionone gave compound 4 in minor amounts, along with acetate 3 (in 1–2 % yield each) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketone 4 , which is a natural product with a pleasant floral scent, was previously synthesized by the palladium‐catalyzed arylation of 2,3,6‐trimethylbromobenzene with 3‐butene‐2‐one . A few examples in the literature have shown that ketone 4 can also be formed directly from ionones . The microbial oxidation of β‐ionone gave compound 4 in minor amounts, along with acetate 3 (in 1–2 % yield each) .…”
Section: Resultsmentioning
confidence: 99%
“…The microbial oxidation of β‐ionone gave compound 4 in minor amounts, along with acetate 3 (in 1–2 % yield each) . More recently, compound 4 was obtained in up to 65 % yield through the stoichiometric oxidation of α‐, β‐, or retro‐ionone with CuCl 2 , FeCl 3 , or substituted BQ (2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone) …”
Section: Resultsmentioning
confidence: 99%
“…Methyl migration and aromatization of conjugate carotenoid systems is important in the biosynthesis of aromatic carotenoids 19 and the same rearrangement can be accomplished by reacting -ionone with 2-4 equivalents CuCl2 (30%) in DMF as solvent, albeit in low yields. 20 It is likely that any build-up of Cu[TPMA]Cl2 in our reaction is responsible for this migration.…”
Section: Scheme 5 Cyclization Of Dienamide 25amentioning
confidence: 94%
“…Spectra in accordance with those described in the literature. 28 To a stirring solution of methyl 2-cyano-3-methylbut-2-enoate (1.36 g, 9.7 mmol, 1 equiv) and acetic anhydride (0.18 mL, 1.9 mmol, 0.2 equiv) in anhydrous toluene (10 mL) was added DMF-DMA (1.6 mL, 11.7 mmol, 1.2 equiv).…”
Section: Methyl (4e)-2-cyano-5-(dimethylamino)-3-methylpenta-24-dienmentioning
confidence: 99%